Low-temperature freeze-resistant mineral cementing material, preparation method and application thereof
The modified carbon nanotube-reinforced multi-component solid waste cementitious material system solves the problems of slow setting and frost heave of mining cementitious materials in low-temperature environments, achieving rapid hardening and improved structural stability, and is suitable for low-temperature mine filling and support.
Patent Information
- Application Number
- CN202611021996.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-11-03
AI Technical Summary
Existing mining cementitious materials exhibit slow hydration reactions, long setting times, insufficient early strength, easy expansion of microcracks due to frost heave, and low strength retention after freeze-thaw cycles in low-temperature environments. Furthermore, they are difficult to adapt to special working conditions such as high solid waste content, high water-cement ratio, and long-distance pipeline transportation.
A modified carbon nanotube-reinforced multi-component solid waste cementing system is adopted, which combines antifreeze and early strength, air-entraining antifreeze and water-retaining antisegregation system. Through the synergistic effect of components such as sulfoaluminate cement clinker, desulfurized gypsum, slag powder and fly ash, CSH and CASH gels are formed, which promote the formation of early structural framework. Modified carbon nanotubes and nanomaterials are used to fill pores and bridge microcracks to control frost heave stress.
It achieves rapid solidification and hardening under low temperature conditions, improves early structural stability and freeze resistance, reduces bleeding and segregation, and enhances the construction adaptability and durability of mine backfill materials. It is suitable for underground backfilling and low temperature support reinforcement in cold mines.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, and in particular to a low-temperature antifreeze cementitious material for mining, its preparation method, and its application. Background Technology
[0002] Cemented backfilling technology in mines is an important technical means for treating tailings, controlling ground pressure, managing goaf areas, and improving the recovery rate of mineral resources. Existing mine backfilling cementitious materials are mostly composed of ordinary silicate cement, slag powder, fly ash, or desulfurized gypsum, which can meet certain backfilling strength requirements under normal temperature conditions.
[0003] However, in cold-region mines or during winter construction, the ambient temperature for slurry preparation, transportation, and backfilling is low, with some areas even remaining below 0°C for extended periods. Low temperatures significantly reduce the hydration rate of cementitious materials, leading to prolonged slurry setting time, slow early strength development, and a loose backfill structure. When the mixing water freezes or partially freezes, it causes slurry volume expansion, increased internal porosity, and the expansion of microcracks, further reducing the later strength and durability of the backfill. Furthermore, mine tailings typically have complex particle sizes, high fine particle content, and some tailings contain sulfates, chlorides, or other corrosive ions, which can negatively impact the long-term stability of the backfill. Traditional cementitious materials, under the combined effects of low temperatures, freeze-thaw cycles, and groundwater erosion, exhibit deficiencies such as insufficient frost resistance, poor crack resistance, significant bleeding and segregation, and insufficient early load-bearing capacity. Existing technologies also include methods to improve the low-temperature performance of cement-based materials by adding antifreeze agents, early-strength agents, or air-entraining agents. However, most of these solutions only target ordinary concrete or mortar systems and do not fully consider the special working conditions of mine backfill materials, such as high solid waste content, high water-cement ratio, long-distance pipeline transportation, and low-temperature setting and hardening. Furthermore, single admixtures often cannot simultaneously solve the problems of slow low-temperature hydration, frost heave cracking, poor slurry stability, and significant strength loss.
[0004] Therefore, it is necessary to develop a mining cementitious material suitable for low-temperature environments. Through the synergistic effect of a multi-component solid waste cementitious system, an antifreeze and early strength system, a nano-reinforcement system, an air-entraining antifreeze system, and a water-retaining and anti-segregation system, the early strength, antifreeze performance, crack resistance, and construction adaptability of mining backfill materials under low-temperature conditions can be improved. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a low-temperature resistant cementitious material for mining, its preparation method, and its application. The modified carbon nanotube-enhanced low-temperature resistant cementitious material provided by this invention effectively solves the problems commonly found in existing mining cementitious materials during mine backfilling and low-temperature construction in cold regions, such as slow low-temperature hydration reaction, long setting and hardening time, insufficient early strength development, easy freezing of mixing water, easy propagation of frost heave microcracks, and low strength retention after freeze-thaw cycles. It exhibits excellent low-temperature adaptability, early structural stability, and freeze-thaw resistance.
[0006] Firstly, this invention provides a low-temperature antifreeze cementitious material for mining. Its core lies in using slag powder, fly ash, steel slag powder, and desulfurized gypsum as solid waste-based cementitious components, and regulating low-temperature activity with sulfoaluminate cement clinker and metakaolin. This is achieved through a synergistic regulation of an antifreeze early-strength system, a modified carbon nanotube / nanooxide composite reinforcement system, an air-entraining system, and a water-retaining thickening system. The active aluminate minerals in the sulfoaluminate cement clinker can react with sulfate ions provided by the desulfurized gypsum, promoting the formation of ettringite-like hydration products. The alkaline environment and calcium source provided by the steel slag powder and sulfoaluminate cement clinker facilitate the participation of active silica-alumina components in the slag powder, fly ash, and metakaolin in the reaction, forming CSH gels and CASH-like gels. By weight, the low-temperature antifreeze mining cementitious material comprises: 30-60 parts slag powder, 12-30 parts fly ash, 5-10 parts desulfurized gypsum, 5-15 parts steel slag powder, 10-20 parts sulfoaluminate cement clinker, 2-8 parts metakaolin, 0.01-1 parts modified carbon nanotubes, 0.1-3 parts nano-silica, 0.1-2 parts nano-alumina, 2-10 parts antifreeze early strength agent, 0.01-1 parts air-entraining agent, and 0.01-1 parts water-retaining thickener. The above components work together to promote early structural framework formation, improve pore structure, and enhance slurry stability under low-temperature conditions.
[0007] Preferably, the modified carbon nanotubes are selected from one or more of carboxylated modified carbon nanotubes, hydroxylated modified carbon nanotubes, silane coupling agent modified carbon nanotubes, and polycarboxylic acid dispersant modified carbon nanotubes; more preferably, they are carboxylated modified carbon nanotubes and / or silane coupling agent modified carbon nanotubes. The surface polar groups are beneficial for improving the dispersibility and interfacial bonding ability of carbon nanotubes in aqueous phases and gel slurries; the modified carbon nanotubes, together with nano-silica and nano-alumina, form a nanocomposite reinforcing system, which can play a role in nucleation, micro-filling, and microcrack bridging, thereby helping to refine the pore size distribution and reduce the propagation of microcracks caused by freeze-thaw heave.
[0008] Preferably, the antifreeze early strength agent includes two or more of calcium nitrate, calcium nitrite, calcium formate, aluminum sulfate, and triethanolamine. More preferably, the antifreeze early strength agent is composed of calcium nitrate, calcium formate, aluminum sulfate, and triethanolamine in a mass ratio of (2~4):(1~3):(1~3):(0.1~0.4), more preferably 3:2:2:0.2; or composed of calcium nitrate, calcium nitrite, calcium formate, and triethanolamine in a mass ratio of (2~4):(1~3):(1~3):(0.1~0.5), more preferably 3:2:2:0.3. Calcium salts and aluminum salts synergistically promote the formation of early hydration products, while triethanolamine is used to regulate the reaction rate of the aluminate phase. The above ratio can balance the low-temperature early strength effect and the workability of the slurry.
[0009] Preferably, the air-entraining agent includes one or more of rosin thermal polymer air-entraining agents, sodium dodecyl sulfate, and fatty alcohol polyoxyethylene ether; more preferably, it is a rosin thermal polymer air-entraining agent, and its dosage is preferably 0.02~0.06 parts. An appropriate amount of air-entraining agent can form relatively uniformly distributed micro-closed bubbles in the hardened body, providing buffer space for ice expansion; controlling it within the above-mentioned preferred dosage range is beneficial to balancing the resistance to frost heave and the strength of the hardened body.
[0010] Preferably, the water-retaining thickener is selected from one or more of hydroxypropyl methylcellulose ether, sodium carboxymethyl cellulose, bentonite, and styrene; more preferably, it is hydroxypropyl methylcellulose ether, or a compound of bentonite and hydroxypropyl methylcellulose ether in a mass ratio of 2:1, or a compound of hydroxypropyl methylcellulose ether and styrene in a mass ratio of 4:1. The above-mentioned water-retaining thickener system can improve the cohesiveness and water retention of the slurry, reducing the risks of bleeding, sedimentation, and segregation during long-distance transportation.
[0011] Preferably, the low-temperature antifreeze mining cementitious material further includes an activator; the activator includes one or more of sodium sulfate, sodium carbonate, sodium silicate, and calcium hydroxide. More preferably, the activator is a compound of sodium sulfate and sodium carbonate in a mass ratio of (1~2):1, or a compound of sodium sulfate and sodium silicate in a mass ratio of 2:1. The activator can increase the early alkalinity and ion concentration of the slurry, promoting the dissolution and reaction of active silica-alumina components in slag powder, fly ash, and metakaolin.
[0012] Preferably, the low-temperature antifreeze mining cementitious material further includes a water-reducing agent, which is one or more of polycarboxylate water-reducing agents, naphthalene-based water-reducing agents, or aminosulfonate water-reducing agents, preferably a polycarboxylate water-reducing agent. Polycarboxylate water-reducing agents can improve powder dispersion and slurry flowability with lower mixing water dosage, and are beneficial for the uniform distribution of nanomaterials in the slurry.
[0013] Further preferred, the low-temperature antifreeze mining cementitious material provided by the present invention comprises the following components by weight: 35-50 parts slag powder; 15-28 parts fly ash; 10-18 parts sulfoaluminate cement clinker; 6-10 parts desulfurized gypsum; 5-12 parts steel slag powder; 3-8 parts metakaolin; 2-6 parts silica fume; 0.05-0.3 parts modified carbon nanotubes; 0.5-2 parts nano silica; 0.2-1 parts nano alumina; 3-8 parts antifreeze early strength agent; 2-6 parts activator; 0.01-0.08 parts air-entraining agent; 0.3-1.2 parts water-reducing agent; and 0.05-0.4 parts water-retaining thickener. This invention employs a certain amount of slag powder, fly ash, steel slag powder, and desulfurized gypsum as the main solid waste-based cementitious components, and sulfoaluminate cement clinker and metakaolin as low-temperature active reinforcing components, together forming a multi-component cementitious system suitable for low-temperature environments. Nano-silica, nano-alumina, and modified carbon nanotubes together constitute a nanocomposite reinforcing system, used to fill the internal pores of the cementitious material, refine the pore size distribution, and improve the strength retention rate after freeze-thaw cycles. By constructing a solid waste-based multi-component cementitious system and combining the synergistic effects of antifreeze and early-strength components, nano-reinforcing components, air-entraining and antifreeze components, and water-retaining and anti-segregation components, the continuous hydration of the cementitious material and the rapid formation of an early structural framework are promoted under low-temperature conditions. In this invention, the synergistic reaction of sulfoaluminate cement clinker, desulfurized gypsum, slag powder, and metakaolin facilitates the generation of hydration products such as ettringite, CSH gel, and CASH gel under low-temperature conditions. Antifreeze and early-strength agents lower the freezing point of the slurry liquid phase and increase the low-temperature hydration rate. Modified carbon nanotubes, nano-silica, and nano-alumina fill pores, bridge microcracks, and regulate the microstructure of the hardened body. Air-entraining agents and water-retaining thickeners improve slurry stability and alleviate frost heave stress. This invention effectively solves the problems of existing mining cementitious materials, such as difficulty in rapid setting and hardening at low temperatures, insufficient early load-bearing capacity, significant structural deterioration after freeze-thaw cycles, and easy bleeding and segregation of the slurry. It also considers the high-volume utilization of industrial solid waste, adaptability to pipeline transportation, and economic efficiency in mine backfilling projects, improving the stability, safety, and durability of this type of cementitious material in applications such as underground backfilling in cold-region mines, tailings cemented backfilling, goaf remediation, and low-temperature support reinforcement.
[0014] Secondly, the present invention provides a method for preparing the aforementioned low-temperature antifreeze mining cementitious material, comprising: 1) Dry slag powder, fly ash, steel slag powder, metakaolin and silica fume to obtain dried solid waste powder; 2) Sulfoaluminate cement clinker and desulfurized gypsum are ground to obtain active cementitious powder; 3) Modified carbon nanotubes, nano-silica and nano-alumina are ultrasonically and / or high-speed sheared in water to obtain a nanocomposite reinforced dispersion; 4) The dried solid waste powder and the active gelling powder are mixed with an antifreeze early-strength agent, an activator, an air-entraining agent, a water-reducing agent, and a water-retaining thickener to obtain a dry powder gelling material; and optionally, the dry powder gelling material is mixed and stirred with the nano-composite reinforced dispersion during construction. This invention employs a staged feeding method to prepare the basic gelling powder and the composite low-temperature antifreeze additive system separately, and then introduces the nano-composite reinforced dispersion to improve the dispersion uniformity of modified carbon nanotubes and nanomaterials in the slurry. The staged feeding and dispersion process ensures that modified carbon nanotubes, nano-silica, and nano-alumina are preferentially distributed in the gelling product formation region, thereby forming a nano-reinforced-gelling product composite structure during low-temperature hardening.
[0015] As a preferred embodiment, the preparation method of the low-temperature antifreeze mining cementitious material includes: drying slag powder, fly ash, steel slag powder, metakaolin, and silica fume; grinding sulfoaluminate cement clinker and desulfurized gypsum to a set fineness to obtain a low-temperature active cementitious component; carboxylating or silane coupling modification of carbon nanotubes and dispersing them with a polycarboxylate dispersant to obtain a modified carbon nanotube dispersion; adding nano-silica and nano-alumina to the modified carbon nanotube dispersion and dispersing them ultrasonically or by high-speed shearing to obtain a nano-composite reinforced dispersion; premixing an antifreeze early-strength agent, an activator, an air-entraining agent, a water-reducing agent, and a water-retaining thickener in a certain proportion to obtain a composite low-temperature antifreeze admixture system; and dry-mixing slag powder, fly ash, sulfoaluminate cement clinker, desulfurized gypsum, steel slag powder, metakaolin, and silica fume evenly to obtain a basic cementitious powder. A composite low-temperature antifreeze admixture system is added to the basic cementitious powder, and the mixture is further mixed evenly to obtain a dry powder type low-temperature antifreeze mining cementitious material. Preferably, the process further includes: during construction, mixing and stirring the dry powder type low-temperature antifreeze mining cementitious material, tailings, water, and nano-composite reinforcing dispersion to obtain a low-temperature antifreeze mining filling slurry, and then performing filling, pouring, or support reinforcement treatment.
[0016] In a further preferred embodiment, the preparation method of the low-temperature antifreeze mining cementitious material includes the following steps: S1. Dry the slag powder, fly ash, steel slag powder, metakaolin and silica fume separately so that their moisture content is not greater than 1.0%.
[0017] S2. Grind sulfoaluminate cement clinker and desulfurized gypsum to achieve a specific surface area of 350~500 m². 2 / kg.
[0018] S3. Add carbon nanotubes to a mixed acid solution of nitric acid and sulfuric acid in a volume ratio of 1:3, stir at 80°C for 2 hours, dilute with deionized water, filter and wash until the pH of the filtrate is 6.5-7.5, then vacuum dry at 60°C for 12 hours to obtain carboxylated carbon nanotubes. This step can be omitted when using commercially available carboxylated carbon nanotubes.
[0019] S4. Carboxylated carbon nanotubes are added to an aqueous solution containing a silane coupling agent and a polycarboxylic acid dispersant, wherein the amount of silane coupling agent is 2% of the mass of the carboxylated carbon nanotubes and the amount of polycarboxylic acid dispersant is 5% of the total mass of the nano-solids; the mixture is ultrasonically dispersed at 40 kHz and 600 W for 30 min, and then stirred at 500 r / min for 1.5 h to obtain a surface-modified carbon nanotube dispersion.
[0020] S5. Add nano-silica and nano-alumina to the modified carbon nanotube dispersion, continue ultrasonic dispersion for 20 min at 40 kHz and 600 W, and shear at 3000 r / min for 10 min to prepare a nano-composite reinforced dispersion with a solid content of 10%.
[0021] S6. Mix calcium nitrate, calcium formate, aluminum sulfate and triethanolamine in a mass ratio of 3:2:2:0.2 for 5 min to obtain an antifreeze and early strength composite admixture.
[0022] S7. Premix the air-entraining agent, water-retaining thickener, and water-reducing agent (20% of the total amount of water-reducing agent) for 3 minutes to obtain the antifreeze-stabilizing and foam-retaining water-retaining component.
[0023] S8. Add slag powder, fly ash, sulfoaluminate cement clinker, desulfurized gypsum, steel slag powder, metakaolin and silica fume into the mixer and dry mix for 5-10 minutes to obtain basic cementitious powder.
[0024] S9. Add antifreeze and early strength composite admixture, activator, antifreeze, foam stabilizing and water-retaining components and remaining water-reducing agent to the basic cementitious powder, and continue mixing for 5-8 minutes to obtain dry powder type low temperature antifreeze mining cementitious material.
[0025] S10. During construction, the dry powder type low-temperature antifreeze mining cementitious material, tailings, and total mixing water are mixed at a mass ratio of 1:4~8:1.5~3. A nano-composite reinforced dispersion with a solid content of 10% and a mass ratio of 0.1~0.2 times that of the cementitious material is added. The water in the dispersion is included in the total mixing water and deducted equally from the additional water. The mixture is first stirred at 60 r / min for 2 min, then at 120 r / min for 3 min to obtain the low-temperature antifreeze mining filling slurry.
[0026] Thirdly, this invention provides the application of the aforementioned low-temperature resistant mining cementitious material or the low-temperature resistant mining cementitious material obtained by the aforementioned preparation method. The low-temperature resistant mining cementitious material is used for cemented backfilling, tailings backfilling, goaf treatment, low-temperature support reinforcement, or the preparation of low-strength controllable materials in mines operating at temperatures ranging from -15°C to 5°C. This invention effectively solves the problems of existing mining cementitious materials, such as difficulty in rapid setting and hardening at low temperatures, insufficient early load-bearing capacity, significant structural deterioration after freeze-thaw cycles, and easy bleeding and segregation of the slurry.
[0027] The beneficial effects of this invention are at least as follows: (1) The sulfoaluminate cement clinker, desulfurized gypsum, slag powder, fly ash, steel slag powder and metakaolin form a multi-component cementitious system, which is conducive to the formation of ettringite, CSH gel and CASH gel under low temperature conditions, and promotes early structure establishment; (2) The antifreeze and early strength composite admixture can regulate the freezing point of the liquid phase and the early hydration reaction, and reduce the slow setting and hardening caused by low temperature; (3) The modified carbon nanotubes, nano silica and nano alumina form a nano-composite reinforcement system, which can play a role in nucleation, micro-filling and micro-crack bridging; (4) The air-entraining agent and water-retaining thickener help to form an appropriate amount of fine closed bubbles, improve the viscosity of the slurry and reduce bleeding and segregation; (5) The material makes extensive use of industrial solid wastes such as fly ash, slag powder, steel slag powder and desulfurized gypsum, which can reduce the amount of clinker raw materials used. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0029] The endpoints and any values of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.
[0030] Unless otherwise specified, the techniques or conditions described in the embodiments of this invention shall be performed in accordance with the techniques or conditions described in the literature in this field, or in accordance with the product instructions. Devices, instruments, reagents, etc., without specified manufacturers, are all conventional products that can be purchased through legitimate channels. All experimental reagents and raw materials involved are commercially available products, and all reagents are analytical grade products.
[0031] In this embodiment of the invention, the following raw material specifications may be used: S95 grade granulated blast furnace slag powder; Grade II fly ash; calcium sulfate dihydrate in desulfurized gypsum with a mass fraction of not less than 90%; and steel slag powder with a specific surface area of 400~450 m². 2 / kg; the specific surface area of sulfoaluminate cement clinker is 400~450 m² / kg. 2 / kg; the total mass fraction of SiO2 and Al2O3 in metakaolin is not less than 85%; the mass fraction of SiO2 in silica fume is not less than 90%; the modified carbon nanotubes are multi-walled carbon nanotubes with an outer diameter of 10-30 nm, a length of 5-20 μm, and a surface carboxyl content of 1.5%-2.5%; the average particle sizes of nano-silica and nano-alumina are 20-30 nm and 30-50 nm, respectively, and the purity of both is not less than 99%; the polycarboxylate superplasticizer is in powder form with a water reduction rate of not less than 25%; the nominal viscosity of hydroxypropyl methylcellulose ether is 100,000 mPa·s. All of the above raw materials can be obtained from commercial channels.
[0032] Example 1 This embodiment provides a modified carbon nanotube-enhanced low-temperature freeze-thaw resistance cementitious material for mining, comprising: 42 parts slag powder, 22 parts fly ash, 14 parts sulfoaluminate cement clinker, 8 parts desulfurized gypsum, 8 parts steel slag powder, 5 parts metakaolin, 3 parts silica fume, 0.10 parts modified carbon nanotubes, 1.0 part nano silica, 0.5 parts nano alumina, 5 parts antifreeze early strength agent, 4 parts activator, 0.04 parts air-entraining agent, 0.6 parts polycarboxylate superplasticizer, and 0.15 parts water-retaining thickener.
[0033] The antifreeze and early strength agent is composed of calcium nitrate, calcium formate, aluminum sulfate and triethanolamine in a mass ratio of 3:2:2:0.2; the activator is composed of sodium sulfate and sodium carbonate in a mass ratio of 2:1; and the water-retaining and thickening agent is hydroxypropyl methylcellulose ether.
[0034] This embodiment was prepared according to the general preparation process described above. The modified carbon nanotubes used were carboxylated multi-walled carbon nanotubes; the antifreeze early-strength agent, activator, air-entraining agent, water-reducing agent, and water-retaining thickener were measured according to the formula. During sample preparation, the mass ratio of cementitious material, tailings, and total mixing water was 1:6:3, and the amount of nanocomposite reinforced dispersion was 0.15 times the mass of the cementitious material, and included in the total mixing water. The resulting slurry was used for low-temperature mine cemented backfilling.
[0035] Example 2 This embodiment provides a modified carbon nanotube-enhanced low-temperature freeze-thaw resistance mining cementitious material, comprising: 38 parts slag powder, 26 parts fly ash, 16 parts sulfoaluminate cement clinker, 7 parts desulfurized gypsum, 6 parts steel slag powder, 4 parts metakaolin, 4 parts silica fume, 0.15 parts modified carbon nanotubes, 1.5 parts nano silica, 0.4 parts nano alumina, 6 parts antifreeze early strength agent, 3 parts activator, 0.05 parts air-entraining agent, 0.8 parts polycarboxylate superplasticizer, and 0.20 parts water-retaining thickener.
[0036] The antifreeze and early strength agent is composed of calcium nitrate, calcium nitrite, calcium formate and triethanolamine in a mass ratio of 3:2:2:0.3; the activator is a mixture of sodium sulfate and sodium silicate; and the water-retaining and thickening agent is composed of bentonite and hydroxypropyl methylcellulose ether in a mass ratio of 2:1.
[0037] The preparation method is the same as in Example 1. When using it, the mass ratio of cementitious material, tailings, and water is 1:6:3.
[0038] Example 3 This embodiment provides a modified carbon nanotube-enhanced low-temperature freeze-thaw resistance cementitious material for mining, comprising: 48 parts slag powder, 18 parts fly ash, 12 parts sulfoaluminate cement clinker, 9 parts desulfurized gypsum, 10 parts steel slag powder, 6 parts metakaolin, 2 parts silica fume, 0.08 parts modified carbon nanotubes, 0.8 parts nano silica, 0.3 parts nano alumina, 4 parts antifreeze early strength agent, 5 parts activator, 0.03 parts air-entraining agent, 0.5 parts polycarboxylate superplasticizer, and 0.10 parts water-retaining thickener.
[0039] The antifreeze and early strength agent is composed of calcium formate, aluminum sulfate and triethanolamine in a mass ratio of 3:2:0.2; the activator is composed of sodium sulfate, sodium carbonate and calcium hydroxide in a mass ratio of 2:1:1; and the water-retaining and thickening agent is sodium carboxymethyl cellulose.
[0040] The preparation method is the same as in Example 1. When using it, the mass ratio of cementitious material, tailings, and water is 1:6:3.
[0041] Example 4 This embodiment provides a modified carbon nanotube-enhanced low-temperature freeze-thaw resistance cementitious material for mining, comprising: 35 parts slag powder, 28 parts fly ash, 18 parts sulfoaluminate cement clinker, 6 parts desulfurized gypsum, 5 parts steel slag powder, 8 parts metakaolin, 5 parts silica fume, 0.20 parts modified carbon nanotubes, 2.0 parts nano silica, 0.8 parts nano alumina, 7 parts antifreeze early strength agent, 3 parts activator, 0.06 parts air-entraining agent, 1.0 part polycarboxylate superplasticizer, and 0.25 parts water-retaining thickener.
[0042] The antifreeze and early strength agent is composed of calcium nitrate, calcium nitrite, calcium formate, aluminum sulfate and triethanolamine in a mass ratio of 3:2:2:2:0.3; the activator is composed of sodium sulfate and sodium carbonate in a mass ratio of 1:1; the air-entraining agent is a rosin thermal polymer air-entraining agent; and the water-retaining and thickening agent is composed of hydroxypropyl methylcellulose ether and styrene in a mass ratio of 4:1.
[0043] The preparation method is the same as in Example 1. When using it, the mass ratio of cementitious material, tailings, and water is 1:6:3.
[0044] Example 5 This embodiment provides a low-temperature antifreeze cementitious material for mining, comprising: 50 parts slag powder, 15 parts fly ash, 10 parts sulfoaluminate cement clinker, 10 parts desulfurized gypsum, 12 parts steel slag powder, 3 parts metakaolin, 2 parts silica fume, 0.05 parts carboxylated modified carbon nanotubes, 0.5 parts nano-silica, 0.2 parts nano-alumina, 3 parts antifreeze early strength agent, 2 parts activator, 0.01 parts sodium dodecyl sulfate, 0.3 parts polycarboxylate superplasticizer, and 0.05 parts sodium carboxymethyl cellulose. The antifreeze early strength agent is composed of calcium nitrate, calcium formate, aluminum sulfate, and triethanolamine in a mass ratio of 3:2:2:0.2; the activator is composed of sodium sulfate and sodium carbonate in a mass ratio of 2:1. The preparation method and sample preparation conditions are the same as in Example 1.
[0045] Example 6 This embodiment provides a low-temperature antifreeze cementitious material for mining, comprising: 35 parts slag powder, 28 parts fly ash, 18 parts sulfoaluminate cement clinker, 6 parts desulfurized gypsum, 5 parts steel slag powder, 8 parts metakaolin, 6 parts silica fume, 0.30 parts silane coupling agent modified carbon nanotubes, 2.0 parts nano silica, 1.0 part nano alumina, 8 parts antifreeze early strength agent, 6 parts activator, 0.08 parts rosin thermal polymer air-entraining agent, 1.2 parts polycarboxylate superplasticizer, and 0.40 parts water-retaining thickener. The antifreeze early strength agent is composed of calcium nitrate, calcium nitrite, calcium formate, aluminum sulfate, and triethanolamine in a mass ratio of 3:2:2:2:0.3; the activator is composed of sodium sulfate, sodium carbonate, and calcium hydroxide in a mass ratio of 2:1:1; and the water-retaining thickener is composed of hydroxypropyl methylcellulose ether and acetone in a mass ratio of 4:1. The preparation method and sample preparation conditions are the same as in Example 1.
[0046] Comparative Example 1 This comparative example is basically the same as Example 1, except that modified carbon nanotubes, nano-silica, and nano-alumina are not added. The cementitious materials include: 42 parts slag powder, 22 parts fly ash, 14 parts sulfoaluminate cement clinker, 8 parts desulfurized gypsum, 8 parts steel slag powder, 5 parts metakaolin, 3 parts silica fume, 5 parts antifreeze early strength agent, 4 parts activator, 0.04 parts air-entraining agent, 0.6 parts polycarboxylate superplasticizer, and 0.15 parts water-retaining thickener.
[0047] Comparative Example 2 This comparative example is basically the same as Example 1, except that no antifreeze and early strength agent is added. The cementitious materials include: 42 parts slag powder, 22 parts fly ash, 14 parts sulfoaluminate cement clinker, 8 parts desulfurized gypsum, 8 parts steel slag powder, 5 parts metakaolin, 3 parts silica fume, 0.10 parts modified carbon nanotubes, 1.0 part nano silica, 0.5 parts nano alumina, 4 parts activator, 0.04 parts air-entraining agent, 0.6 parts polycarboxylate superplasticizer, and 0.15 parts water-retaining and thickening agent.
[0048] Comparative Example 3 This comparative example is basically the same as Example 1, except that: it does not use a staged preparation and nanocomposite enhanced dispersion process; instead, it uses ordinary homogenization and stirring by adding all powder, additives, tailings and water into a mixer at once.
[0049] The data obtained after the above tests are shown in Table 1. Table 1. Test results of Examples 1-6 and Comparative Examples 1-3
[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low-temperature resistant cementitious material for mining, characterized in that, By weight, it includes the following raw materials: 30-60 parts slag powder; 12-30 parts fly ash; 5-10 parts desulfurized gypsum; 5-15 parts steel slag powder; 10-20 parts sulfoaluminate cement clinker; and 2-8 parts metakaolin. 0.01~1 part of modified carbon nanotubes; 0.1-3 parts of nano silica; 0.1-2 parts of nano alumina; 2-10 parts of antifreeze and early strength agent; 0.01-1 parts of air-entraining agent and 0.01-1 parts of water-retaining and thickening agent.
2. The low-temperature antifreeze mining cementitious material according to claim 1, characterized in that, The modified carbon nanotubes are selected from one or more of carboxylated modified carbon nanotubes, hydroxylated modified carbon nanotubes, silane coupling agent modified carbon nanotubes, and polycarboxylic acid dispersant modified carbon nanotubes.
3. The low-temperature antifreeze mining cementitious material according to claim 1 or 2, characterized in that, The antifreeze and early strength agent includes two or more of calcium nitrate, calcium nitrite, calcium formate, aluminum sulfate, and triethanolamine.
4. The low-temperature antifreeze mining cementitious material according to any one of claims 1-3, characterized in that, The air-entraining agent includes one or more of the following: rosin thermal polymer air-entraining agents, sodium dodecyl sulfate, and fatty alcohol polyoxyethylene ether.
5. The low-temperature antifreeze mining cementitious material according to any one of claims 1-4, characterized in that, The water-retaining and thickening agent is selected from one or more of hydroxypropyl methylcellulose ether, sodium carboxymethyl cellulose, bentonite, and styrene.
6. The low-temperature antifreeze mining cementitious material according to any one of claims 1-5, characterized in that, It also includes an activator; the activator includes one or more of sodium sulfate, sodium carbonate, sodium silicate, and calcium hydroxide.
7. The low-temperature antifreeze mining cementitious material according to any one of claims 1-6, characterized in that, It also includes a water-reducing agent, which is one or more of polycarboxylate water-reducing agents, naphthalene-based water-reducing agents, or aminosulfonate water-reducing agents.
8. The low-temperature antifreeze mining cementitious material according to any one of claims 1-7, characterized in that, By weight, it includes the following components: 35-50 parts slag powder; 15-28 parts fly ash; 10-18 parts sulfoaluminate cement clinker; 6-10 parts desulfurized gypsum; 5-12 parts steel slag powder; 3-8 parts metakaolin; 2-6 parts silica fume; and 0.05-0.3 parts modified carbon nanotubes. Nano silica 0.5-2 parts; nano alumina 0.2-1 parts; antifreeze and early strength agent 3-8 parts; activator 2-6 parts; air-entraining agent 0.01-0.08 parts; water-reducing agent 0.3-1.2 parts; 0.05~0.4 parts of water-retaining thickener.
9. A method for preparing the low-temperature antifreeze mining cementitious material according to any one of claims 1-8, characterized in that, include: 1) Dry slag powder, fly ash, steel slag powder, metakaolin and silica fume to obtain dried solid waste powder; 2) Sulfoaluminate cement clinker and desulfurized gypsum are ground to obtain active cementitious powder; 3) Modified carbon nanotubes, nano-silica and nano-alumina are ultrasonically and / or high-speed sheared in water to obtain a nanocomposite reinforced dispersion; 4) The dried solid waste powder and the active gelling powder are mixed with an antifreeze early strength agent, an activator, an air-entraining agent, a water-reducing agent and a water-retaining thickener to obtain a dry powder gelling material; and optionally, the dry powder gelling material is mixed and stirred with the nano-composite reinforced dispersion during construction.
10. The application of the low-temperature antifreeze mining cementitious material according to any one of claims 1 to 8 or the low-temperature antifreeze mining cementitious material obtained by the preparation method according to claim 9, characterized in that, Used for the preparation of cemented backfill, tailings backfill, goaf treatment, low-temperature support and reinforcement, or low-strength controllable materials in mines at temperatures ranging from -15 to 5℃.
